Comments on the paper "Petrography and mineralogy of the white marble and black stone of Göktepe (Muğla, Turkey) used in antiquity: New data for provenance determination" by M. Brilli, M.P. Lapuente Mercadal, F. Giustini and H. Royo Plumed (JAS Reports 2018, 19, 625–642). (April 2020) - Attanasio, D.; Bruno, M.; Prochaska, W.; Yavuz, A.B.
Highlights: Analyses recently published on Göktepe marbles are shown to be erroneous. High Sr and low Mn concentrations are re-affirmed to be typical of Göktepe marbles. Current provenancing procedures based on these and other variables are confirmed. Abstract: Referring to an article recently published by JAS Reports (Brilli et al., 2018, 19, 625-642) this communication raises doubts and poses questions concerning the identity and origin of the materials used for the analyses and the reliability of the results that are presented. Very different analytical values, in fact, were already reported for several samples that are now re-published using different labels. The point is crucial because new data may entangle the identification of an important ancient marble.